2017
DOI: 10.1002/pssb.201700256
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Interaction Between Spherical Aerogels of Multi‐Walled Carbon Nanotubes

Abstract: Lightweight materials for efficient electromagnetic interference shielding over a wide range of frequency are of great interest. Aerogels of multi-walled carbon nanotubes (MWCNTs) distributed in a dielectric matrix may interact effectively with electromagnetic radiation. Moreover, being arranged in specific patterns, they can also provide metamaterial characteristics (e.g., negative refractive index). In the present paper, we have studied the interaction between two spheres of the carbon nanotube aerogels in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Carbon nanotubes (CNTs) are among the key nanostructures that have been actively developed and investigated during the last two decades due to their unique electrophysical properties, such as high electrical and thermal conductivity, high mechanical strength, relative chemical inertness, the ability to absorb electromagnetic radiation over a wide range of wavelengths, etc. CNTs are considered as promising candidates for many potential applications such as nanocomposite materials, catalyst and catalyst supports, field emitters, sensors, energy storage devices, hydrogen storage, fuel cells, nanoelectronics, bionanomaterials, and nanomedicine . Generally, most of multi‐walled carbon nanotubes (MWCNTs) are used to improve the physical and chemical characteristics of numerous composite materials based on polymeric, metal and oxide matrices .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) are among the key nanostructures that have been actively developed and investigated during the last two decades due to their unique electrophysical properties, such as high electrical and thermal conductivity, high mechanical strength, relative chemical inertness, the ability to absorb electromagnetic radiation over a wide range of wavelengths, etc. CNTs are considered as promising candidates for many potential applications such as nanocomposite materials, catalyst and catalyst supports, field emitters, sensors, energy storage devices, hydrogen storage, fuel cells, nanoelectronics, bionanomaterials, and nanomedicine . Generally, most of multi‐walled carbon nanotubes (MWCNTs) are used to improve the physical and chemical characteristics of numerous composite materials based on polymeric, metal and oxide matrices .…”
Section: Introductionmentioning
confidence: 99%
“…It was interesting to compare this value with any independent data on the average distance between nanotubes in the aerogel. Unfortunately the analysis of average distances between MWCNTs using SEM images of aerogel is a complex task that requires obtaining tomographic images and extremely time‐consuming statistical analysis due to the tangled structure of curved nanotubes. So we used the analysis based on the volume fraction of nanotubes.…”
Section: Experiments On An Aerogel and Simulation Resultsmentioning
confidence: 99%
“…This model is semi‐empirical since the experimentally determined polarizability of a spherical sample is used to estimate the electrophysical parameters of the aerogel environment. An experimental study of spherical aerogels in the gigahertz range (8–12 GHz) showed that, despite the high conductivity of CNTs in the aerogel media and high density of their packages compared to the wavelength, effective parameters of aerogels noticeably differ from those of metals.…”
Section: Introductionmentioning
confidence: 99%
“…There are known models of a regular wire medium formed by macroscopic conductors, whereas for nanoscale objects such models are not available. We propose to construct such models by applying a macroscopic approach to nanoscale copper conductors, since their electrophysical properties are known and experimentally confirmed . The problem is that the wire medium models use bulk conductors, while the MWCNTs are considered as 2D objects, so a transition to some effective conductivity is required.…”
Section: Methodsmentioning
confidence: 99%